Preparation method of spherical Co3O4-coated Cu3Mo2O9 nano-film electrode material
Through the preparation of spherical Co3O4@Cu3Mo2O9 nano-film electrode material, the problem of low electron transfer rate of Co3O4 electrode material in supercapacitor is solved, high specific capacitance and good cycling stability are achieved, and the overall performance of the supercapacitor is improved.
Patent Information
- Application Number
- CN202411363901.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing supercapacitors have shortcomings in cyclic stability and overall efficiency. Co3O4, as an electrode material, has a low electron transfer rate during the reaction, which affects its electrochemical performance.
The spherical Co3O4@Cu3Mo2O9 nano-film electrode material was used to prepare the material on foam nickel by hydrothermal deposition. Cu3Mo2O9 is combined with Co3O4 to improve electrochemical performance, provide a larger specific surface area and shorter diffusion path, and promote electrolyte ion penetration. To inhibit NiCo2O4 reunion.
Achieve high specific capacitance (942F g-1) and good cycling stability (capacity retention rate up to 80.59%), with an energy density of 40Wh Kg-1 at 800W Kg-1, showing excellent electrochemical performance and fast charging Discharge capability.
Smart Images

Figure CN119208028A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a method for preparing a spherical Co3O4@Cu3Mo2O9 nano-thin film electrode material. Background Art
[0002] Increasing environmental pollution and dwindling renewable energy supplies highlight the urgent need to develop materials required for next-generation energy storage solutions. Supercapacitors and lithium-ion batteries have become key players in the field of electrochemical energy storage, among which supercapacitors have attracted the attention of researchers due to their superior power density, ultra-long cycle life and fast charging capabilities. These supercapacitors can be divided into electric double-layer capacitors (EDLCs) and pseudocapacitors based on different charge storage mechanisms. EDLCs store energy by separating charges at the electrode / electrolyte interface, while pseudocapacitors rely on Faradaic redox reactions to store energy. Although supercapacitors offer significant benefits, their current applications are limited and improvements are needed in terms of cycle stability and overall efficiency. The effectiveness and performance of supercapacitors depend on the structural design and electrochemical properties of the electrode materials used.
[0003] Transition metal oxides (TMOs) have attracted great attention among these materials due to their different oxidation states, sample preparation methods, and high theoretical specific capacitance. Various metal oxides such as MnO2, NiO, Fe2O3, and Co3O4 have been used as electrode materials for supercapacitors. Among them, Co3O4 has the advantages of high theoretical capacitance, low cost, environmental friendliness, and high electrochemical stability, and is considered to be the preferred electrode material for supercapacitors. However, in practical applications, Co3O4 exhibits a low electron transfer rate during the reaction, which weakens its electrochemical performance. Summary of the invention
[0004] In view of the above technical problems, the present invention proposes a method for preparing spherical Co3O4@Cu3Mo2O9 nanofilm electrode materials. Molybdenum-based oxide Cu3Mo2O9 has strong catalytic properties. The composite of Cu3Mo2O9 and Co3O4 can promote the electrochemical reaction of the positive electrode material and improve the electrochemical performance of the positive electrode material. The reason is that the spherical structure after composite provides a relatively large specific surface area, more reaction sites and a shorter diffusion path length, so that the electrolyte ions can easily and quickly penetrate the electrode material, resulting in low resistance, thereby improving the electrochemical performance. In addition, Co3O4 can provide a large open space as a framework that is conducive to the formation of Cu3Mo2O9, and successfully inhibits the agglomeration of NiCo2O4, which is also conducive to the improvement of electrochemical performance. .
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a spherical Co3O4@Cu3Mo2O9 nanofilm electrode material comprises the following steps:
[0007] Dissolve Co(NO3)2·6H2O and urea in deionized water to obtain a red solution, add nickel foam to the red solution, heat it in a hydrothermal reactor, cool it naturally to room temperature, wash it, dry it, and calcine it to obtain Co3O4 / / nickel foam electrode material;
[0008] Cu(NO3)2·6H2O and NaMoO4 are added to deionized water to obtain a uniform solution (Cu3Mo2O9), the Co3O4 / / nickel foam electrode material is immersed in the uniform solution, heated again in a hydrothermal reactor, naturally cooled to room temperature, washed, dried, and calcined again to obtain a Co3O4@Cu3Mo2O9 nanofilm electrode material.
[0009] Furthermore, in the red solution, the usage ratio of Co(NO3)2·6H2O, urea and deionized water is 0.4g:0.3g:50mL.
[0010] Furthermore, the heating conditions are: temperature 130° C., time 5 h; the calcination conditions are: heating rate 3° C. / min, temperature 320° C., time 2 h.
[0011] Furthermore, in the homogeneous solution, the dosage ratio of Cu(NO3)2·6H2O, NaMoO4 and deionized water is 0.31 g:0.28 g:30 mL.
[0012] Furthermore, the conditions for the reheating treatment are: temperature 160° C., time 6 h; the conditions for the re-calcination are: heating rate 3° C. / min, temperature 400° C., time 2 h.
[0013] The present invention also provides a spherical Co3O4@Cu3Mo2O9 nano film electrode material prepared by the above preparation method.
[0014] The present invention also provides an application of the spherical Co3O4@Cu3Mo2O9 nano-film electrode material in preparing a supercapacitor.
[0015] Compared with the prior art, the present invention has the following advantages and technical effects:
[0016] The present invention successfully prepared a binder-free Co3O4@Cu3Mo2O9 thin film electrode material on nickel foam by using a simple hydrothermal deposition method. The electrode exhibited excellent electrochemical performance.-1 942F g -1 The assembled Co3O4@Cu3Mo2O9 / / AC supercapacitor has a power density of 800W Kg -1 The energy density is 40Wh Kg -1 ,In addition, after 5000 cycles, the capacity retention rate of Co3O4@Cu3Mo2O9 / / AC reached up to 80.59%, indicating good ,cycling stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0018] Figure 1 a is the SEM image (30 μm) of Co3O4@Cu3Mo2O9; b is the SEM image (10 μm) of Co3O4@Cu3Mo2O9; c is the EDS image of Co3O4@Cu3Mo2O9;
[0019] Figure 2 a is the XRD diffraction pattern of Co3O4, Co3O4@Cu3Mo2O9, and Cu3Mo2O9; b is the XPS spectrum of Co3O4@Cu3Mo2O9; c is the Mo 3d high-resolution x-ray photoelectron spectrum of Co3O4@Cu3Mo2O9; d is the Co 2p high-resolution x-ray photoelectron spectrum of Co3O4@Cu3Mo2O9; e is the Cu 2p high-resolution x-ray photoelectron spectrum of Co3O4@Cu3Mo2O9; f is the O1s high-resolution x-ray photoelectron spectrum of Co3O4@Cu3Mo2O9;
[0020] Figure 3 a is the nitrogen adsorption-desorption curve of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9; b is the pore size distribution curve of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9; c is the contact angle of Co3O4; d is the contact angle of Cu3Mo2O9; e is the contact angle of Co3O4@Cu3Mo2O9;
[0021] Figure 4 a is the CV curve of Co3O4@Cu3Mo2O9 at different scan rates; b is the comparison of CV curves of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 at the same potential window and scan rate; c is the comparison of CV curves of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 at 1.0Ag -1GCD curve under different current density; d is the GCD curve of Co3O4@Cu3Mo2O9 at different current density; e is the specific capacitance of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 at different current density; f is the Nyquist plot of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9;
[0022] Figure 5 a is the CV curve of Co3O4@Cu3Mo2O9 and AC electrode materials; b is the CV curve of Co3O4@Cu3Mo2O9 / / AC device at different voltage windows; c is the CV curve of Co3O4@Cu3Mo2O9 / / AC device at different scan rates; d is the GCD curve of Co3O4@Cu3Mo2O9 / / AC device at different current densities; e is the GCD curve of Co3O4 / / AC device, Cu3Mo2O9 / / AC device and Co3O4@Cu3Mo2O9 / / AC device at 10Ag -1 f is the GCD curve of Co3O4 / / AC device, Cu3Mo2O9 / / AC device and Co3O4@Cu3Mo2O9 / / AC device; g is the energy density and power density curve of Co3O4@Cu3Mo2O9 / / AC device; h is the cycle stability test of Co3O4 / / AC device, Cu3Mo2O9 / / AC device and Co3O4@Cu3Mo2O9 / / AC device;
[0023] Figure 6 a is the relationship between the peak current and scan rate of Co3O4@Cu3Mo2O9 / / AC; b is the ACCV curve of Co3O4@Cu3Mo2O9 showing 50mV s -1 Contribution of capacitance under scanning rate; c is the relative contribution of diffusion and capacitance under different scanning rates of Co3O4@Cu3Mo2O9 / / AC. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0030] The raw materials used in the present invention are all purchased from the market.
[0031] The technical solution of the present invention is further illustrated by the following embodiments.
[0032] Example 1
[0033] Preparation of Co3O4 electrode materials:
[0034] 0.437 g Co(NO3)2·6H2O and 0.312 g urea were dissolved in 50 mL deionized water to form a uniform red solution. Foamed nickel (1 cm×2 cm, NF) was added to the red solution and the whole was placed in a 100 mL hydrothermal reactor and heated to 130°C. After keeping warm for 5 hours, it was naturally cooled to room temperature. The sample was taken out, washed with deionized water, and dried at 60°C for 2 hours. After drying, it was placed in a muffle furnace for calcination, heated to 320°C at a heating rate of 3°C / min and calcined for 2 hours to obtain Co3O4 / / NF electrode material.
[0035] Preparation of Co3O4@Cu3Mo2O9 electrode material:
[0036] 0.31 g Cu(NO3)2·6H2O and 0.28 g NaMoO4 were added to 30 mL deionized water to mix into a uniform solution. The Co3O4 / / NF electrode material was immersed in the above solution and transferred to a 50 mL hydrothermal reactor and kept at 160°C for 6 h. After naturally cooling to room temperature, the sample was taken out, washed with deionized water, and dried at 60°C. Finally, the sample was heated to 400°C in a muffle furnace at a heating rate of 3°C / min and calcined for 2 h to obtain Co3O4@Cu3Mo2O9.
[0037] Control group 1
[0038] Preparation of Cu3Mo2O9 electrode material:
[0039] 0.31 g Cu(NO3)2·6H2O and 0.28 g NaMoO4 were added to 30 mL deionized water and mixed into a uniform solution. Foamed nickel (1 cm×2 cm, NF) was immersed in the above solution and transferred to a 50 mL hydrothermal reactor and kept at 160°C for 6 h. After naturally cooling to room temperature, the sample was taken out, washed with deionized water, and dried at 60°C. Finally, the sample was heated to 400°C in a muffle furnace at a heating rate of 3°C / min and calcined for 2 h to obtain Cu3Mo2O9.
[0040] Figure 1 a (30 μm) and b (10 μm) are SEM images of Co3O4@Cu3Mo2O9 at different magnifications. It can be seen from a and b that the microstructure of Co3O4@Cu3Mo2O9 presents porous spherical characteristics. The porous spherical structure is conducive to the accumulation and transfer of charges. c is the EDS image of Co3O4@Cu3Mo2O9. The EDS spectrum shows that Co, Cu, Mo and O elements are evenly distributed on Co3O4@Cu3Mo2O9.
[0041] The purity and crystal structure information of the samples were analyzed by X-ray diffraction (XRD).
[0042] Figure 2 a in the figure is the XRD diffraction pattern of the prepared samples Co3O4, Co3O4@Cu3Mo2O9 and Cu3Mo2O9. It can be seen that the diffraction peaks of the samples are sharp and clear, and no extra peaks are observed, confirming that Co3O4@Cu3Mo2O9 is composed of Co3O4 and Cu3Mo2O9. b is the XPS spectrum of Co3O4@Cu3Mo2O9, which confirms the presence of Cu, Co, Mo and O elements. High-resolution x-ray photoelectron spectroscopy was used to fit Co3O4@Cu3Mo2O9. From Figure 2As can be seen from the figure, in Co3O4@Cu3Mo2O9, the Mo3d spectrum consists of two main peaks, which can be attributed to Mo 3d 5 / 2 and Mo 3d 3 / 2 The spin-orbit splitting peaks at binding energies of 232.4 and 235.3 eV, respectively. These peaks confirm that Mo 6+ and Mo 4+ The existence of the state. Figure 2 As can be seen from the figure, the Co 2p spectrum has two main peaks at 779.6 and 795.8 eV, which are respectively 2+ and Co 3+ There are also two satellite peaks at 784.2 and 801.9 eV. Figure 2 It can be seen from the e in the Cu 2p spectrum that Cu 2p 3 / 2 and Cu 2p 1 / 2 The two main peaks are located at 934.6 and 954.7 eV, and the satellite peaks are located at 942.8 and 962.7 eV, confirming that Cu 2+ The existence of the state. Figure 2 As can be seen from the figure, the high-resolution O1s spectrum shows three peaks centered at 530.2, 530.8, and 531.9 eV. The peak at 530.2 eV is mainly due to the O attached to Co-O and Cu and Mo atoms. 2- The peak at 530.8 eV is attributed to the Mo-O bond, and the peak at 531.9 eV is attributed to the surface hydroxyl group.
[0043] In order to further explore the pore size distribution and specific surface area of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9, nitrogen adsorption and desorption tests were carried out on the samples. The pore size distribution was analyzed using the BJH model. The results are as follows Figure 3 As shown in b. According to the BJH adsorption curve ( Figure 3 From a), we know that the pore size of Co3O4@Cu3Mo2O9 is mainly between 5-20nm, which proves that the main forms of pores in the sample are micropores and small-sized mesopores. Figure 3 a in the figure is the nitrogen adsorption and desorption test results of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9. Co3O4@Cu3Mo2O9 shows obvious IV type curve characteristics and H4 type hysteresis loop, which proves that there are a large number of micropores in the material. In addition, the wettability of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 was tested by contact angle, such as Figure 3 As shown in Figure c, compared with Co3O4 and Cu3Mo2O9, Co3O4@Cu3Mo2O9 has the smallest contact angle of 38.15°, which indicates that Co3O4@Cu3Mo2O9 has the best wettability.
[0044] Electrochemical tests were carried out on the flower-ball-shaped Co3O4@Cu3Mo2O9 material. The electrode material was subjected to CV tests in 6M KOH aqueous solution at room temperature, and the test potential window was 0-0.5V. Figure 4 Figure a is the CV curve of Co3O4@Cu3Mo2O9 electrode material at different scanning rates. It can be seen from the curve that as the scan progresses, the current peaks of the cathode and anode move toward the two poles and the current of the CV curve increases in direct proportion to the increase in the scan rate, indicating that the material has the characteristics of fast charging and discharging. Figure 4 b in the figure is the potential window and scan rate of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 at the same potential window (0-0.45 V potential window, 100 mV s -1 Scan rate) CV curve comparison chart. From the curve shape and enclosed area, it can be seen that Co3O4@Cu3Mo2O9 has the largest specific capacity. Compared with Co3O4 and Cu3Mo2O9, the shape of Co3O4@Cu3Mo2O9 is more like a rectangle, and the redox peak is widened, indicating that its capacitance is caused by the joint action of pseudocapacitance and double-layer capacitance mechanism. The reason for the widening of the peak may be the superposition of the redox peaks of Co3O4 and Cu3Mo2O9. The composite material is a multi-layer core-shell structure, and the main capacitance is provided by the two active substances Co3O4 and Cu3Mo2O9. Figure 4 c is the electrode materials of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 at 1.0A g -1 From the GCD curve under current density, it can be clearly observed that the discharge time of Co3O4@Cu3Mo2O9 is much longer than that of the other two types of materials. It can also be confirmed that Co3O4 loaded with Cu3Mo2O9 can improve the specific capacitance of the material. The GCD curve of Co3O4@Cu3Mo2O9 is more like the superposition of the GCD curves of Co3O4 and Cu3Mo2O9. Through analysis, both Co3O4 and Cu3Mo2O9 can contribute to the overall specific capacity of the material. The synergistic effect between multiple active substances has achieved electrochemical performance higher than that of a single material. The multi-level "shell-core" structure is conducive to improving the interfacial activity between the electrode material and the electrolyte, making the redox reaction richer. Figure 4 Figure d is the GCD curve of Co3O4@Cu3Mo2O9 at different current densities. It can be seen that the discharge time of Co3O4@Cu3Mo2O9 curve is the longest. Figure 4Figure e is the specific capacitance of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9 at different current densities. It can be seen that the specific capacitance of Co3O4@Cu3Mo2O9 (942F / g) is much larger than that of Co3O4, (329F / g)Cu3Mo2O9 (221F / g). Figure f is the Nyquist plot of Co3O4, Cu3Mo2O9 and Co3O4@Cu3Mo2O9. It can be seen that the slope of the curve of Co3O4@Cu3Mo2O9 is the largest, indicating the smallest impedance.
[0045] Before assembling the Co3O4@Cu3Mo2O9 / / AC device, the prepared positive and negative electrode materials need to be tested by CV. First, the negative electrode is tested by CV in the voltage window of -1 to 0V. The results are as follows: Figure 5 As shown in a in the figure. It can be seen from Figure a that the CV curve of the negative electrode material AC / NF has no obvious redox peak, which indicates that the AC / NF material has obvious double-layer capacitance characteristics. The electrochemical performance of the assembled asymmetric supercapacitor Co3O4@Cu3Mo2O9 / / AC was tested in a double-electrode system. Figure 5 As can be seen from figure b, the device has an obvious redox peak in the voltage window of 0-1.5V. This is caused by the redox reaction of the positive electrode material. When the voltage value continues to increase, the electrode material is polarized and the CV curve is significantly deformed, which will be detrimental to the charge and ion transfer process. Therefore, the voltage window of the device is set in the range of 0-1.5V. The device was subjected to CV and GCD tests in the voltage window of 0-1.5V. It can be seen from figure c that with the increase of the scan rate, the CV curve maintains a relatively consistent shape, indicating that the device has good rate performance. From the GCD test in figure d, it can be seen that the curve has a relatively symmetrical shape, which indicates that the device has a high coulombic efficiency and electrochemical reversibility. At 1.0A g -1 Co3O4 / / AC, Cu3Mo2O9 / / AC and Co3O4@Cu3Mo2O9 / / AC were compared. As can be seen from Figure e, Co3O4@Cu3Mo2O9 / / AC has the longest discharge time, which can be attributed to the synergistic effect between Co3O4 and Cu3Mo2O9. In addition, the conductivity of the three devices Co3O4 / / AC, Cu3Mo2O9 / / AC and Co3O4@Cu3Mo2O9 / / AC was tested. As shown in Figure f, Co3O4@Cu3Mo2O9 / / AC has the best conductivity. The energy density and power density of Co3O4@Cu3Mo2O9 / / AC were calculated by the formula. As can be seen from Figure g, at 800W Kg -1 When Co3O4@Cu3Mo2O9 / / AC has 40Wh Kg -1In addition, the cycle stability of Co3O4 / / AC, Cu3Mo2O9 / / AC and Co3O4@Cu3Mo2O9 / / AC was further tested. It can be seen from Figure h that after 5000 cycles, the capacity retention rate of Co3O4@Cu3Mo2O9 / / AC was the highest (Co3O4@Cu3Mo2O9 / / AC: 80.59%, Co3O4 / / AC: 50%, Cu3Mo2O9 / / AC: 60.45%), which shows that Co3O4@Cu3Mo2O9 / / AC has good cycle stability.
[0046] The charge storage mechanism of the supercapacitor device can be qualitatively determined by the peak current at different scan rates, calculated using the following formula (1).
[0047] i=av b #(1)
[0048] In the equation, i(A) represents the peak current, v(mV s -1 ) represents the scan rate, and a and b are a pair of constants. When b is close to 0.5, it means that the electrode follows the diffusion-controlled charge storage mechanism, and when b is close to 1, it means that the electrode follows the surface-controlled charge storage mechanism. Figure 6 As shown in a, the redox peak current is linearly fitted (the slope is represented by b), and the slopes of the redox peak current are 0.87 and 0.82, respectively. This shows that the device exhibits diffusion and capacitance jointly controlled charge storage behavior. In order to further understand the contribution of surface capacitance and diffusion controlled capacitance at a specific scan rate, the following formula (2) can be used for calculation
[0049]
[0050] Where i represents the response current, k1 and k2 are adjustable parameters, and v (mV s -1 ) represents the voltage scan rate. k1v represents the contribution of surface control current to capacitance. Figure 6 The scan rate is 50 mV s -1 The yellow CV curve represents the capacitance contribution. Figure 6 Figure c shows the 5-100mV s -1 It can be seen that the contribution of capacitance gradually increases from 39% to 73% with the increase of scan rate, which indicates that the device is diffusion controlled at low scan rate, but as the scan rate increases, the charge storage mechanism tends to capacitance controlled behavior.
[0051] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a spherical Co3O4@Cu3Mo2O9 nanofilm electrode material, characterized in that: The following steps are involved: Dissolve Co(NO3)2·6H2O and urea in deionized water to obtain a red solution, add nickel foam to the red solution, heat it in a hydrothermal reactor, cool it naturally to room temperature, wash it, dry it, and calcine it to obtain Co3O4 / / nickel foam electrode material; Cu(NO3)2·6H2O and NaMoO4 are added into deionized water to obtain a uniform solution, the Co3O4 / / nickel foam electrode material is immersed in the uniform solution, heated again in a hydrothermal reactor, naturally cooled to room temperature, washed, dried, and calcined again to obtain a Co3O4@Cu3Mo2O9 nanofilm electrode material.
2. The method for preparing the spherical Co3O4@Cu3Mo2O9 nano-thin film electrode material according to claim 1, characterized in that: In the red solution, the usage ratio of Co(NO3)2·6H2O, urea and deionized water is 0.4g:0.3g:50mL.
3. The method for preparing the spherical Co3O4@Cu3Mo2O9 nano-thin film electrode material according to claim 1, characterized in that: The heating conditions are: temperature 130° C., time 5 h; the calcination conditions are: heating rate 3° C. / min, temperature 320° C., time 2 h.
4. The method for preparing the spherical Co3O4@Cu3Mo2O9 nano-thin film electrode material according to claim 1, characterized in that: In the homogeneous solution, the dosage ratio of Cu(NO3)2·6H2O, NaMoO4 and deionized water is 0.31 g:0.28 g:30 mL.
5. The method for preparing the spherical Co3O4@Cu3Mo2O9 nano-thin film electrode material according to claim 1, characterized in that: The conditions for the reheating treatment are: temperature 160° C., time 6 h; the conditions for the re-calcination are: heating rate 3° C. / min, temperature 400° C., time 2 h.
6. A spherical Co3O4@Cu3Mo2O9 nanofilm electrode material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the spherical Co3O4@Cu3Mo2O9 nanofilm electrode material as claimed in claim 6 in the preparation of supercapacitors.
Citation Information
Patent Citations
Molybdenum disulfide@ZIF-67@CoO-NF composite material as well as synthesis method and application thereof
CN113130216A
Co-Mo-O / Co-O / NF multi-layer composite structure material and preparation method and application thereof
CN117690731A
